A numerical study of dust deposition effects on photovoltaic modules and photovoltaic-thermal systems. (May 2019) - Salari, Ali; Hakkaki-Fard, Ali
Abstract: Dust deposition on the surface of solar systems is one of the main parameters that significantly affects the performance of such systems. In this study, the effect of dust deposition density on the performance of photovoltaic modules (PV) and photovoltaic-thermal systems (PVT) is numerically investigated. Accordingly, all layers of a monocrystalline silicon PV module for both systems are simulated. Moreover, the effect of various system parameters on the performance of both clean and dusty PV module and PVT system are studied. The studied parameters included: solar radiation intensity, ambient temperature, coolant inlet temperature, and coolant inlet velocity. The obtained results indicate that by increasing the dust deposition density on the surface of the PV module from 0 g/m 2 to 8 g/m 2, its electrical efficiency reduces by 26.36%. In addition, by increasing the dust deposition density on the surface of the PVT system from 0 g/m 2 to 8 g/m 2, its electrical and thermal efficiencies reduce by 26.42% and 16.11%, respectively. Moreover, the simulation results show that the effect of considered parameters on the clean solar system is more significant than the dusty system. Furthermore, two correlations for electrical and thermal output reduction as a function of dust deposition density are proposed. Highlights: Numerical simulations of PV module and PVT system are performed. Numerical results are validated against experimental results. The effect of dust deposition densities on the electrical and thermal performances of PV module and PVT system are studied. By increasing dust deposition density of PV module from 0 g/m 2 to 8 g/m 2, its electrical efficiency reduces by 26.36%.